Psychological adaptation of mature women in the first days after mastectomy - Bąk-Sosnowska, Monika; Oleszko, Kinga; Skrzypulec-Plinta, Violetta (Menopause Review/Przegląd Menopauzalny, 2013)
Aim of the study: The evaluation of the psychological adaptation of women in the first days after mastectomy and the impact of selected factors on the process of acceptance of the disease. Material and methods: Thirty-two women were examined. The mean age was 64.5 ±0.7 years. A questionnaire, AIS scale, and Mini MAC Scale were used. Results : The dominant emotion was fear. The sense of physical attractiveness decreased, while the sense of closeness towards a partner increased. The biggest support was provided by the medical staff. The acceptance of the disease was lower in comparison with women suffering from breast or uterine cancer (t = –3.20; p < 0.01). The respondents differed in the level of acceptance of the disease depending on the intensity of support obtained from their families (χ2 = 12.45; p < 0.01). Fifty-two percent (R2 = 0.516) of the acceptance of the disease is explained by the family support (β = 0.56; p < 0.001), and anxiety (β = –0.38; p < 0.01). The respondents showed worse adjustment to illness than women suffering from breast cancer in the sense of preoccupation with anxiety (t = –2.53; p < 0.05) and helplessness (t = –2.12; p < 0.05), but better results in the category of fighting spirit (t = 5.99; p < 0.001). A relation between acceptance of the illness and preoccupation with anxiety (r = –0.42; p < 0.05) and positive redefinition (r = 0.43; p < 0.05) was demonstrated. Conclusions : The reduction in anxiety and increase in family support promote the acceptance of the disease. The more acceptance of the disease, the less anxiety and the more positive valuation of disease.